ANALYSIS OF THE SUPREME COURT DECISION NO. 119 PK/Pdt.Sus-HKI/2017 ON TRADEMARK DISPUTES FROM THE PERSPECTIVE OF HAQ AL-IBTIKAR - Muhammad Qeis; Muhammad Syuib; T. Surya Reza (JURISTA: Jurnal Hukum dan Keadilan, 2026)
Trademark protection is an integral part of the intellectual property system that protects a product's reputation, economic value, and identity. According to Article 3 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, trademark protection is only granted to registered trademarks. However, in practice, trademark infringement has occurred, as in Supreme Court Decision Number 119 PK/Pdt.Sus-HKI/2017, between PT Gudang Garam as the owner of the well-known trademark "Gudang Garam" and the party using the trademark "Gudang Baru" on cigarette products. The method used was a normative legal approach, with a conceptual lens, examining case studies and literature as data collection techniques. The results of the survey show that PT Gudang Garam initially lost at the first level and in cassation because the judge considered the registration of the Gudang Baru trademark to be administratively valid. However, through a case review (PK), the Supreme Court found bad faith and similarity in essence, so that Gudang Garam ultimately won the case. This shows that the protection of well-known trademarks still faces challenges in terms of evidence in court. From the perspective of Haq al-Ibtikar, such actions constitute the unlawful taking of another person’s rights, which is prohibited under Sharia law, because trademarks are intellectual works with practical and economic value. It is recommended that trademark rights be protected preventively through official registration, market monitoring, and legal education for business actors, as well as strict law enforcement against trademark registrations made in bad faith.